2020
DOI: 10.1021/acsptsci.0c00106
|View full text |Cite
|
Sign up to set email alerts
|

An Enzymatic TMPRSS2 Assay for Assessment of Clinical Candidates and Discovery of Inhibitors as Potential Treatment of COVID-19

Abstract: SARS-CoV-2 is the viral pathogen causing the COVID19 global pandemic. Consequently, much research has gone into the development of preclinical assays for the discovery of new or repurposing of FDA-approved therapies. Preventing viral entry into a host cell would be an effective antiviral strategy. One mechanism for SARS-CoV-2 entry occurs when the spike protein on the surface of SARS-CoV-2 binds to an ACE2 receptor followed by cleavage at two cut sites (“priming”) that causes a conformational change allowing f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
132
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(152 citation statements)
references
References 54 publications
16
132
1
1
Order By: Relevance
“…We are fairly confident to postulate that these favorable results are unlikely due to inhibition of TMPRSS2, although we can’t fully exclude extremely weak activity. This view is supported by a recent study that found no effect of Bromhexine on TMPRSS2 activity (30). More likely, favorable patient outcomes are attributable to the beneficial effects of Bromhexine or its main metabolite Ambroxol on lung function, general defense mechanisms against airway infections, and inflammatory response (16–19, 50).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…We are fairly confident to postulate that these favorable results are unlikely due to inhibition of TMPRSS2, although we can’t fully exclude extremely weak activity. This view is supported by a recent study that found no effect of Bromhexine on TMPRSS2 activity (30). More likely, favorable patient outcomes are attributable to the beneficial effects of Bromhexine or its main metabolite Ambroxol on lung function, general defense mechanisms against airway infections, and inflammatory response (16–19, 50).…”
Section: Discussionsupporting
confidence: 59%
“…As fusion effectors, SARS1-S, SARS2-S as well as SARS2-S1/S2-mut and SARS2-S2′-AA were included. To test the effects of TMPRSS2 inhibition by small molecules on the activation of wt SARS2-S and the two mutants as well as SARS1-S, we incubated the different target cells with Bromhexine, reportedly a specific inhibitor of TMPRSS2 (15), the chemically related compound Ambroxol, or Camostat, an irreversible inhibitor of TMPRSS2 and many serine proteases in general (29, 30), at 50 µM (Fig. 3 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of small molecules of interest for treating COVID-19 that are currently in clinical trials were not hits in our assay. For example, the TMPRSS2 inhibitors camostat and nafamstat are protease inhibitors approved in Japan for treating pancreatitis, and known to inhibit TMPRSS2 ( Shrimp et al, 2020 ). While TMPRSS2 is reported to be a mediator of SARS-CoV-2 cell entry, Vero E6 cells do not express TMPRSS2, so this class of compound are not active in the Vero E6 assay.…”
Section: Discussionmentioning
confidence: 99%
“…In order to uncover the molecular activity hypothesis of these medicines and provide evidence that can help advance them further, Tim Hempel et al have combined cell-based assays, detailed molecular experiments, and Markov modeling [ 95 ]. Prior studies provided evidence that both blockers work directly on Transmembrane serine protease 2 (TMPRSS2) and that Nafamostat is more active than Camostat, and this qualitative discrepancy is consistent with additional purified protein and cell-entry assays in addition to in vitro assays [ 28 , 96 , 97 ]. Tim Hempel et al observe that between such three assay forms, the absolute IC50 s amounts differ, indicating variations in experimental parameters and which feature has been inhibited and calculated.…”
Section: Nafamostat Mesylatementioning
confidence: 83%